Caregiving Burden And Depression Among Caregivers Of Patient With Epilepsy (Journal of Psychiatrists' Association of Nepal, 2019)
Introduction: The impact of caregiving on caregivers is a significant area to be studied which will directly affect the quality of care given by them to patients with epilepsy. Family caregivers have been described as forgotten patients. The aim of the study was to assess the caregiving burden and depression among caregivers of patient with epilepsy.Material and Method: Descriptive study was conducted among 100 caregivers of adult patients with epilepsy. Samples were selected using purposive sampling. Semi-structured interview schedule, Zarit Burden Interview (ZBI) and Hamilton depression rating scale (HAM-D) were used for data collection. Data was analyzed by descriptive and inferential statistics with SPSS version 20.Results: Among 100 caregivers, 42% reported high mean burden scores on the ZBI and overall 50% of caregivers reported moderate depression on the HAM-D. High level of burden was significantly associated with age of caregivers (p= 0.018) and caregivers’ relationship with patients (p= 0.023). The result suggests that there was statistically significant positive relationship on ZBI vs HAM-D (p≤ 0.01).Conclusion: Caregivers of patients with epilepsy experience significant burden while caring for their relatives and level of burden is positively correlated with depression. The study highlights the need for comprehensive care system recognizing caregivers as “co-client”.